2010
DOI: 10.1073/pnas.0914187107
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome arm length and nuclear constraints determine the dynamic relationship of yeast subtelomeres

Abstract: Physical interactions between distinct chromosomal genomic loci are important for genomic functions including recombination and gene expression, but the mechanisms by which these interactions occur remain obscure. Using telomeric association as a model system, we analyzed here the in vivo organization of chromosome ends of haploid yeast cells during interphase. We separately labeled most of the 32 subtelomeres and analyzed their positions both in nuclear space and relative to three representative reference sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
177
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(215 citation statements)
references
References 41 publications
37
177
1
Order By: Relevance
“…This organization largely favours interaction between centromeric proximal sequences as well as contact between subtelomeres (Bystricky et al 2005;Schober et al 2008;Therizols et al 2010;Duan et al 2010;Agmon et al 2013). Consistently, recombination between centromeres on one hand and between subtelomeric sequences on the other hand occurs efficiently (Burgess and Kleckner 1999;Brown et al 2010;Agmon et al 2013;Lee et al 2016).…”
Section: Finding a Homologous Sequence Is A Challenge In The Nuclear mentioning
confidence: 53%
“…This organization largely favours interaction between centromeric proximal sequences as well as contact between subtelomeres (Bystricky et al 2005;Schober et al 2008;Therizols et al 2010;Duan et al 2010;Agmon et al 2013). Consistently, recombination between centromeres on one hand and between subtelomeric sequences on the other hand occurs efficiently (Burgess and Kleckner 1999;Brown et al 2010;Agmon et al 2013;Lee et al 2016).…”
Section: Finding a Homologous Sequence Is A Challenge In The Nuclear mentioning
confidence: 53%
“…Clustering is a dynamic process where individual telomeres split from clusters and rejoin on a time scale of minutes (Schober et al 2008). Telomeres at the ends of chromosome arms of similar length associate with one another more frequently, owing to the comigration of centromeres at anaphase (Schober et al 2008;Therizols et al 2010). Interestingly, long-lived stationary-phase cells group all telomeres into a single Sir3-dependent cluster, a genomic restructuring event that extends chronological life span (Guidi et al 2015).…”
Section: Dynamic Nuclear Compartmentalization Of Silent Chromatinmentioning
confidence: 99%
“…Structural data obtained by statistical positioning of a gene in a yeast cell population led to a surprisingly simple model to define yeast nuclear architecture (Zimmer and Fabre 2011): Chromosome position can be predicted by a few parameters such as genomic arm length, telomeres (TEL), and centromeres (CEN) tethered to the NE via nuclear-envelope-tethered proteins and to the SPB via microtubules, respectively (Bystricky et al 2005;Therizols et al 2010;Zimmer and Fabre 2011). This description was recently complemented by the first Hi-C comprehensive maps (Rodley et al 2009;Duan et al 2010), which confirmed an organization guided by nuclear landmarks, including TEL that congregate in foci (Gotta et al 1996;Schober et al 2008).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%